2021
DOI: 10.1017/s0376892920000521
|View full text |Cite
|
Sign up to set email alerts
|

Specimens of opportunity provide vital information for research and conservation regarding elusive whale species

Abstract: Summary Elusive species are challenging to study and conserve because basic elements of their biology may be unknown. Specimens of opportunity provide a means of collecting information on these species and may be critical for elusive species’ conservation. We used snowball sampling to identify Sowerby’s beaked whale (Mesoplodon bidens) specimens in museums and research institutions. Snowball sampling proved highly effective: we located 180 specimens from 24 institutions in North America and Europe, 62 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The results of this study provide the first stable isotope evidence for spatial structuring in Sowerby's beaked whale. Coupled with previously identified morphological differences in skull measurements (Smith et al, 2021), our results suggest that Sowerby's beaked whale exhibits a metapopulation structure of two or more populations with limited movement of individuals between regions. However, genetic analysis is also needed to further explore whether these are distinct population segments or if this is a panmictic species with habitat preference among individuals and regional mixing for mating.…”
Section: Spatial Population Structuringsupporting
confidence: 84%
See 1 more Smart Citation
“…The results of this study provide the first stable isotope evidence for spatial structuring in Sowerby's beaked whale. Coupled with previously identified morphological differences in skull measurements (Smith et al, 2021), our results suggest that Sowerby's beaked whale exhibits a metapopulation structure of two or more populations with limited movement of individuals between regions. However, genetic analysis is also needed to further explore whether these are distinct population segments or if this is a panmictic species with habitat preference among individuals and regional mixing for mating.…”
Section: Spatial Population Structuringsupporting
confidence: 84%
“…Site fidelity has been recorded in other beaked whales, such as Cuvier's (Ziphius cavirostris) and Blainville's (M. densirostris), but this has not been investigated or documented in Sowerby's beaked whale (McSweeney et al, 2007). Analysis of seven cranial elements from 112 Sowerby's beaked whale museum specimens identified significant morphological differences between specimens collected in the east and west Atlantic Ocean, suggesting there may be distinct populations of Sowerby's beaked whale (Smith et al, 2021). However, mitochondrial DNA analysis of 14 individuals identified both regionally distinct and shared haplotypes between animals collected from both sides of the Atlantic Ocean (COSEWIC, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…MacLeod et al (2006) identified the value of stranded carcasses and museum collections of ziphiid specimens as an important source of data for research. Smith et al (2021) collated information from museum skeletal collections of Sowerby's Beaked Whales worldwide (including specimens reported here) to reveal new findings about the species. Unfortunately, only a minority (34.5%) of dead eastern Canadian ziphiids have had skeletons, tissue, parasites, stomach contents, or anatomical parts deposited in publicly accessible museum collections.…”
Section: Ziphiid Strandings In Eastern Canada and Conservation Researchmentioning
confidence: 99%
“…Important summer areas have been identified using bottom-mounted autonomous acoustic recorders. Possible calving areas have been described off Western Ireland [11,55,56] and stabile isotope analysis suggests that there may be several populations of SBWs [3,4]. Efforts to study live and dead SBWs in proximity to the Skagerrak basin would provide additional insights into SBWs in the Northeastern Atlantic.…”
Section: Historical Records Of Sbwsmentioning
confidence: 99%
“…Sowerby's beaked whales (Mesoplodon bidens (Sowerby, 1804), SBW) have the most northerly range of Mesoplodon beaked whale species in the Atlantic Ocean, but their distribution, biology and threats are not fully understood [1,2]. Recent studies have found morphological differences between SBWs from the western and eastern North Atlantic, suggesting a metapopulation structure or several populations within the species [3,4]. Thus, intra-species differences regarding their ecology, behaviour or migrations may exist.…”
Section: Introductionmentioning
confidence: 99%